Aneurysm Packing with HydroCoil Embolic System versus Platinum Coils: Initial Clinical Experience - Cloft, Harry J.; Kallmes, David F. (American Journal of Neuroradiology, 2004)
Summary: The HydroCoil Embolic System (HES; MicroVention, Aliso Viejo, CA) was developed to improve the efficacy of endovascular treatment of cerebral aneurysms. The HES may reduce recurrences of aneurysms by allowing for increased packing density as compared with platinum coils. We report our initial experience with the HES in the treatment of 11 patients with cerebral aneurysms and compare findings to those in size-matched control cases treated with platinum coils. The HES provided substantially improved volumetric packing of the aneurysm lumen relative to standard platinum coils (73% vs. 32%; P=.0001).